Rural households’ demand for domestic energy in Odeda Local Government Area (LGA) of Ogun State, Nigeria (2012)
The nature of demand for domestic energy influences environmental conservation and sustainable development. This study determined the factors influencing expenditures on energy products by rural households. Data were collected from 130 randomly sampled households. Analysis was done with descriptive statistics and Tobit regression. Results show that the largest proportion of the respondents was using kerosene for cooking and lighting. Tobit regression results show that as household heads grow older, their demand for charcoal and kerosene significantly increased (p<0.10). Households that were using fuel wood for cooking were spending less on kerosene and electricity (p<0.05). Also, decision to use each of the energy types for cooking significantly increased the demand (p<0.01). It was recommended that efforts to address energy problem in the rural area should take cognizance of ensuring availability and affordability of cleaner energy sources.